A catalogue of the Antarctic and sub-Antarctic Phoxocephalidae (Crustacea: Amphipoda: Gammaridea) with taxonomic, distribution and ecological data - Alonso, Gloria Maria (2008)
An up-to-date catalogue of Antarctic and sub-Antarctic Phoxocephalidae is presented, including 35 species. Extensive list of bibliographical references with synonymy, detailed information on geographic and bathymetric distribution, ecological data, museum locations of type-material, remarks on taxonomic and biogeographical status, are provided for each species. The catalogue is based on taxonomic and ecological literature until 31 December 2006. Additional unpublished records of species from the Antarctic and sub-Antarctic collections held at the Alfred Wegener Institut für Polar- und Meeresforschung, Bremerhaven, and at the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Buenos Aires, have been included. The taxonomic status of all the Southern Ocean species has been checked. Species allocated to the genera Paraphoxus and Parharpinia, and Fuegiphoxus uncinatus require further study to clarify or confirm the genus allocation. Most of the Southern Ocean phoxocephalids have a wide bathymetric distribution, equally present in the Antarctic and sub-Antarctic regions. The highest species richness is found above 200 meters depth in the sub-Antarctic region. Of 35 phoxocephalid species reported, 25 are endemic to the Southern Ocean s.l., 15 are endemic to the Antarctic region and 6 are endemic to the sub-Antarctic region, the latter distributed only in the Magellan province. Endemicity at genus level attains 22% for the whole Southern Ocean, with 3 genera restricted to the Magellan province and one genus to the West Antarctic, Magellan and sub-Antarctic islands provinces. Habitat and substrate preferences, dietary and burrowing behaviours are scarcely known for most of the phoxocephalid species from the Southern Ocean.